Comparing the thermo-physical characteristics of lard and selected plant fats - Abdul Manaf, Yanty Noorzianna; Marikkar, Jalaldeen Mohammed Nazrim; Mat Sahri, Miskandar (Consejo Superior de Investigaciones Cientificas, 2012)
A comparison of the thermo-physical properties of lard and plant fats may help to formulate alternative fat substitutes for halal food applications. In this study, plant-based fats, namely avocado butter (Persea americana), cocoa butter (Theobroma cacao L.), palm oil (Elaeis guinensis) and mee fat (Madhuca longifolia) are compared to lard with respect to the basic physico-chemical parameters, fatty acid and triacylglycerol (TAG) compositions, and melting and solidification behaviors. Although plant fats are completely different from lard with respect to fatty acid and TAG compositions, they share some common thermal features with lard. Based on thermal analysis, lard and plant fats, except cocoa butter, are found to have thermal transitions in both low (< 0 °C) and high (> 0 °C) melting regions of their cooling and melting curves. According to pulse NMR data, mee fat and lard are found to display closely similar solidification profiles in the temperature range of 0-25 °C, while palm oil and lard are found to have similar solidification profiles in the temperature range between 25-40 °C. Hence, the thermo-physical property comparison between plant fats and lard may be useful to formulate a fat blend which simulates the thermal properties of lard.